THEORETICAL PERSPECTIVES AND CONCEPTUAL FRAMEWORKS OF COOPETITION - Suzanna Lamria Siregar (Universitas Gunadarma, 2009)
There are several perspectives that provide useful theoretical frameworks for analyzing coopetition based on its original paradigm – competition and cooperation. They are transaction–cost economics, resource-based view, game theory, industrial-organization, socioeconomics and social network analysis. Theoretical perspectives then developed to conceptual frameworks that explain and predict empirical phenomena of coopetition. The frameworks of coopetition vary from a continuum with cooperation and competition at its ends to the tendency to adopt multidimensionality under orthogonal structure between two constructs of competition and cooperation. Briefly drawing the typology of coopetition with coopetition and cooperation constructs as its axis.Keywords: coopetition, theoretical perxpectives